The effect of epidural analgesia on postpartum urinary incontinence: a systematic review - Mafalda de Barros Seara Cardoso (2021)
Urinary incontinence (UI) is common during pregnancy and in the postpartum period. Some women appear to recover their usual urinary function but in others UI persists, playing an important role in women's quality of life. Even though postpartum UI seems to have a multifactorial etiology, pregnancy, vaginal delivery, birth weight and parity are recognized as risk factors. This systematic review aims to evaluate the effect of one particular potential risk factor, epidural analgesia, on the development of postpartum UI in women with vaginal delivery. PubMed, Cochrane and Scopus were searched for "epidural analgesia", "epidural anesthesia" or "epidural" and "urinary incontinence". All studies published until July 31st of 2020 were considered. A total of 393 studies were identified and twenty-three studies were included in the systematic review. From the total 23 articles included in this review, 21 showed a non-significant association between epidural analgesia and postpartum UI. One study found that the risk of postpartum SUI and any type of UI was significantly, but only slightly, increased in women with epidural analgesia. Another study showed a protective effect but was lacking control for important confounders. There appears to be no association between epidural analgesia and postpartum UI. For that reason, pregnant women should not fear epidural analgesia because of a possible increased risk of UI.